FORMATION OF A MODEL OF PATRIOTIC EDUCATION OF STUDENTS IN THE EDUCATIONAL ENVIRONMENT OF THE HIGHER MILITARY EDUCATIONAL INSTITUTION - Kameniuk, Yu. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article highlights the process of development and substantiation of the model of patriotic education of cadets in the educational environment of a higher military educational institution, which consists of five interrelated components: target; diagnostic; design; organizational; control and evaluation. The model was developed taking into account the requirements of system, activity, axiological, historical and diagnostic approaches. A component-by-component description of the model is made and the directions of further research are outlined. The target block determines the main purpose of patriotic education of cadets. The diagnostic block highlights the procedure for conducting a confirmatory experiment and methods of studying the level of patriotism of servicemen. The design block of the formed model is intended for creation of psychological and pedagogical conditions of formation of patriotism of cadets, and also for development of necessary tools. The result of the design block is the Target program for the formation of patriotism of servicemen "Patriot of Ukraine". The organizational unit shows the procedure for carrying out the activities of the Target Program. The control and evaluation unit of the model was formed in order to organize control, evaluation of results and further correction of the Target Program for the formation of patriotism in cadets. For a qualitative assessment of the measures, a system of criteria and indicators of patriotism has been defined and described. It is emphasized that the most important achievement of the proposed model is the integrity of information on the process of forming the patriotism of cadets. The directions of further researches, which consist in carrying out research and experimental work on formation of patriotism of servicemen and approbation of the Target program of formation of patriotism of servicemen "Patriot of Ukraine" in educational process of higher military educational institution are defined.